Offshoring information technology : sourcing and outsourcing to a global workforce - Carmel, Erran (Cambridge University Press, 2005)
This book explains everything you need to know to put IT offshoring (outsourcing overseas) into practice, avoid cultural and political pitfalls and develop effective working relationships. Written for CTOs, CIOs, consultants and other IT executives, this book is also an excellent introduction to outsourcing for business and MIS students.